CORRELATION BETWEEN SOCIAL NETWORKING ACTIVITY AND STKIP PGRI TRENGGALEK STUDENTS’ WRITING SKILL - Lya Febriana Yunita Rohma; Sri Utami Dewi; Yulia Nugrahini (STKIP PGRI Trenggalek, 2018)
This study was designed to find whether there is a correlation between social networking activity and students writing skill. There was fifty-two (52) respondent from the sixth semester at STKIP PGRI Trenggalek in academic year 2017/2018 chosen by purposive sampling. The quantitative approach and correlative design were applied in this study. The data was obtained using two instruments, questionnaire of Guttmann scale for social networking activity and test in the form of descriptive for writing skill variable. Calculation using Pearson Product Moment by SPSS program showed between the two variables was 0.842. The conclusion of this study was there is ‘very strong' correlation between social networking activity and students' writing skill of the English Department at STKIP PGRI Trenggalek in academic year 2017/2018.